Physiological Effects of Teucrium polium Extract Ameliorates Ovalbumin-Induced Allergy in Rabbits - Aleem H.A. Nassar (Journal of Global Pharma Technology, 2016)
Objective: This present study aims to evaluation the effectiveness of T.polium extract and compares with oral corticosteroid drug (prednisolone) for reducing signs and symptoms of ovalbumin-induced allergy in rabbits. Also, to detect and confirm the use of T.polium as anti-allergic agent and to weather extent may replace as an herbal therapy instead of oral corticosteroids. Methods : Ovalbumin was used to induce allergy and sensitization challenge was confirmed by the presence of the clinical symptoms of sneezing, wheezing and shortness of breath, chest tightness, changes in the levels of eosinophils, neutrophils, Immunoglobulin E, Interleukin-4. Eight days after allergy induction, Teucrium polium in a dose of (4, 8 and 12 mg/kg) was administrated orally for eight days.  Blood samples were collected at day 15, 30 of the experiment and complete blood count, IgE, IL-4 and levels were determined. Results: showed that ovalbumin could induce sensitivity and significantly increased eosinophils, Immunoglobulin E and Interleukin-4 levels (p≤ 0.05). Oral treatment with Teucrium polium showed a significant decrease in the number of eosinophils (p≤ 0.05) and serum levels of Immunoglobulin E and Interleukin-4 (p≤0.05).  The effects of this plant extract were comparable to those observed in the prednisolone-treated group.Conclusion: Teucrium polium extract have significant results in preventing allergic complications and diminish allergic symptoms especially in asthmatic condition, Also, produced a significant decrease in total WBCs Neutrophils, Eosinophils, IgE and IL 4 on contrast with oral corticosteroid causes dimargination of neutrophils and a significant increase in total white blood cells.Keywords: Teucrium polium; Asthma; Ovalbumin; Interleukin 4 and immunoglobulin E.